2023
DOI: 10.3847/1538-4357/acd182
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of f(R, T) Modified Gravity on the Mass and Radius of Pulsar HerX1

Abstract: Millisecond pulsars are the perfect testable to examine potential matter-geometry coupling and its physical consequences in the context of the recent Neutron Star Interior Composition Explorer discoveries. We apply the field equations of modified gravity, f(R, T) = R + α T, to a spherically symmetric spacetime, where R is the Ricci scalar, α is a dimensional parameter, and T is the matter of the geometry. Five unknown functions are present in the output system of differential equations, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 139 publications
0
7
0
Order By: Relevance
“…In spite of the capability of the model to lower the speed of sound in comparison to the GR or quadratic gravity with positive ϵ cases, it is still above the conjectured conformal upper bound on the maximum sound speed c 2 s = c 2 /3. This result may favor matter-geometry nonminimal coupling scenario to provide better framework for treating that issue as suggested by [26,37,84].…”
Section: Jcap09(2023)038mentioning
confidence: 89%
“…In spite of the capability of the model to lower the speed of sound in comparison to the GR or quadratic gravity with positive ϵ cases, it is still above the conjectured conformal upper bound on the maximum sound speed c 2 s = c 2 /3. This result may favor matter-geometry nonminimal coupling scenario to provide better framework for treating that issue as suggested by [26,37,84].…”
Section: Jcap09(2023)038mentioning
confidence: 89%
“…Multiple minimal/non-minimal models have been proposed in this scenario, among them   x + 2 gained great attention in the literature due to its linear nature. Nashed [11] discussed various pulsars in this linear gravity model and solved the differential equations by making an explicit assumption regarding the anisotropy and radial component of the metric. They found that the estimated masses of these pulsars are in accordance with the observed ones.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Harko and collaborators [57] proposed another extension of standard GR, the f (R, T) modified gravity theories, where the gravitational Lagrangian is given by an arbitrary function of the Ricci scalar R and of the trace of the energy-momentum tensor T. The cosmological consequences [58][59][60][61][62][63][64][65][66][67][68][69] and applications to compact stars [70][71][72][73][74][75][76][77][78][79][80][81][82][83] of such a theory have been addressed by several authors in recent years. See further [84][85][86][87] for a novel scalar-tensor representation of f (R, T) gravity.…”
Section: Introductionmentioning
confidence: 99%